DIFFERENCES IN DENTAL CALCULUS INDICES AND SALIVARY CALCIUM AND PHOSPHATE LEVELS IN CHILDREN WITH CHRONIC KIDNEY DISEASE UNDERGOING HEMODIALYSIS AND PERITONEAL DIALYSIS THERAPY - Kirana, Thea; Sutadi, Heriandi; B Budiardjo, Sarworini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to analyze the differences in dental calculus indices and calcium and phosphate levels in children with chronic kidney disease undergoing hemodialysis (HD) and peritoneal dialysis (PD) therapy. Methods: In this cross-sectional study, 15 children undergoing HD therapy and 15 undergoing PD therapy were subjected to intraoral examination for dental calculus indices. Whole unstimulated saliva samples of all subjects were collected and subjected to calcium and phosphate analysis. Statistical analyses were conducted using the Mann–Whitney and independent t-tests. Results: The dental calculus indices were significantly lower and salivary calcium level was significantly higher in the PD group than those in the HD group (p<0.05). The salivary phosphate level was lower in the PD group (p≥0.05) but without significance. Conclusion: The PD group had lower dental calculus indices and higher salivary calcium level. The higher salivary phosphate levels in the HD group may have contribute to the higher dental calculus indices, probably because phosphate plays an important role in dental calculus formation.